PENGEMBANGAN VIDEO ANIMASI BERBASIS DISCOVERY LEARNING UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK KELAS III SD - Putri, Risna Estuning; Munaris, Munaris; Pramudiyanti, Pramudiyanti (Center for Research and Community Service (LPPM) University of Abulyatama, 2025)
This study aims to develop and examine the effectiveness of an animated video based on the Discovery Learning model to improve Indonesian language learning outcomes among third-grade students at UPTD SDN 2 Adijaya. The research employed the 4D development model, consisting of the Define, Design, Develop, and Disseminate stages. A total of 30 students participated in the study. The problem identified in the classroom was the students’ low understanding of the use of capital letters, which was attributed to the less engaging conventional teaching methods. To address this issue, a Discovery Learning-based animated video was developed as a learning medium. The product was validated by content, language, and media experts, who found it feasible for classroom use with several revisions to improve visual clarity and language accuracy. Trial results showed an improvement in student learning outcomes and engagement during the learning process. Therefore, the Discovery Learning-based animated video proved to be effective in supporting students’ understanding of Indonesian language material, particularly the correct use of capital letters, and serves as an innovative and engaging learning media alternative for third-grade primary school students